2020
DOI: 10.3390/foods9030280
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Ash and Moisture in Wheat Flour by Raman Spectroscopy

Abstract: Wheat flour is widely used on an industrial scale in baked goods, pasta, food concentrates, and confectionaries. Ash content and moisture can serve as important indicators of the wheat flour’s quality and use, but the routinely applied assessment methods are laborious. Partial least squares regression models, obtained using Raman spectra of flour samples and the results of reference gravimetric analysis, allow for fast and reliable determination of ash and moisture in wheat flour, with relative standard errors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 20 publications
1
31
0
1
Order By: Relevance
“…Statistically significant changes in dry matter content were also observed-an increasing proportion of bagasse was associated with an increase in dry matter. This is consistent with the results of the study by Czaja et al, who showed that the water content of wheat flour ranges from 9.0% to 15.0% [39], so it is higher than that of chokeberry pomace (about 5.0%). In the studied products, fat came only from the addition of butter, so the fat content of the different variants of shortcrust pastries was similar.…”
Section: Nutritional Valuesupporting
confidence: 93%
“…Statistically significant changes in dry matter content were also observed-an increasing proportion of bagasse was associated with an increase in dry matter. This is consistent with the results of the study by Czaja et al, who showed that the water content of wheat flour ranges from 9.0% to 15.0% [39], so it is higher than that of chokeberry pomace (about 5.0%). In the studied products, fat came only from the addition of butter, so the fat content of the different variants of shortcrust pastries was similar.…”
Section: Nutritional Valuesupporting
confidence: 93%
“…Ash content in flour is among the parameter taken in consideration in the assessment of flour quality and defining its use in baked products. High amount of ash in flour can affect its technical quality because of a darker color and greater activity of proteolytic and amylolytic enzymes (Czaja et al, 2020). The ash of the SP flours ranged from 1.22 to 1.48% which complies with the regulatory standard of not more than 1.5 g/100 g (Alamu et al, 2021).…”
Section: Proximate Compositionmentioning
confidence: 77%
“…A spectral region 1300–1700 cm −1 were assigned to protein content, whereas a band connected with ash content was very difficult to find. There were also trials to use Raman spectroscopy to determine ash and moisture in a wheat flour [ 129 ]. Analysis of Raman spectra and reference data combined with partial least squares (PLS) regression models allowed for fast and reliable determination of these two parameters with standard error of prediction was ca.…”
Section: Application Of Spectroscopic Methods In Wheat Products Tementioning
confidence: 99%